Effectiveness of Iron Chelation Therapy Using Serum Ferritin Levels in Thalassemia Major Patients - Anwar, Irum; Amanat, Samina; Khalid, Ahmareen (International Journal of Pathology, 2018)
Objective: Is to evaluate the effectiveness of iron chelation therapy in thalassemia patients using serum ferritin level at children hospital, Shaheed Zulfiquar Ali Bhutto Medical University, Pakistan Institute of Medical Sciences IslamabadBackground: -Thalassemia major is caused by defect in the synthesis of 1 or more the goblin subunits of hemoglobin, resulting in valuable phenol types lifelong RBC transfusion remain the main treatment for BETA thalassemia major patients’ transfusion dependent patients in the absence of chelation therapy, develop progressive accumulation of iron, which is responsible for tissue damage. Prevalence of iron Induce organ damage ultimately resulting in iron toxicity. This iron toxicity produces myocardial siderosis and heart failure, liver cirrhosis and liver fibrosis and liver cancer osteoporosis and endocrine dysfunction and thromboembolism.Materials & Methods: -The study was carried out at thalassemia center, children hospital, Pakistan Institute of Medical Sciences Islamabad January 2015-April 2016. All the patients that are enrolled in the thalassemia center were examined the Inclusion criteria of my study is those patients that are receiving iron chelation therapy. The exclusion criteria of my study are patients that are not undergoing iron chelation therapy.Results:-Out of total 105 patients, 70 (67%) were receiving iron chelation therapy. in these 65(62%) and 40(38%) were males and females respectively. Majority of the patients showed very high ferritin level. The mean serum ferritin level was found to be 3650.14 ng/ml. 65% of the patients have mean serum ferritin level less than 3000ng/ml, 27% of the patients have serum ferritin level between 3000-6000ng/ml, while 8% have ferritin level above 6000ng/ml. The observed highest average ferritin level is 7651ng/ml, while lowest is 1866ng/dl.Conclusion:-A high percentage of the patients are receiving iron chelation therapy in PIMS but iron chelation therapy is not very effective. The study showed high levels of serum ferritin .There is a dire need to rationalize the iron chelation therapy.